Kinerja Pegawai dalam Meningkatkan Pelayanan Publik di Kantor Desa Ranah Baru Kecamatan Kampar Kabupaten Kampar - Anisa Syaputri; Khairul Amri (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Service is an effort to help prepare, or take care of the needs of others. the performance of Ranah Baru village government employees in providing good public services to the community and can be seen from the Performance Indicators, whether the service has reached these indicators by village office employees in providing public services to the community. This study aims to determine the Performance of Employees in Improving Public Services in Ranah Baru Village office, Kampar District, Kampar Regency and to find out the inhibiting factors. This study uses the theory of Levine et al which consists of 3 indicators namely, Responsiveness, Responsibility, Accountability. The method used in this research is a descriptive qualitative research method. With data collection techniques, namely interviews, observation, and documentation. The result of this study is that the performance of employees in improving public services can be said to be not optimal. It is also known that the discipline of the Ranah Baru village office staff cannot be said well, the limited human resources in terms of quality and the lack of electronic media in the form of computers so that the performance of employees in providing services is experiencing delays. In connection with this, it is recommended that the government of the Ranah Baru village office, Kampar District, implement the SOP (Standard Operational Procedure) system, improve discipline and infrastructure, so that in the future the services provided to the community will get better.